Family Support for The Fulfillment of Nutrition of Tuberculosis Patients - Suprajitno Suprajitno; Nunung Rahayu Ningsih (STIKes Patria Husada Blitar, 2018)
Family support covered informational support, instrumental support, emotional support, and appraisal support needed tuberculosis patients, including support of nutrition fulfillment.Â The study aimed to know the correlation of information obtained and the family support to the fulfillment of nutrition of tuberculosis patients. The study used correlation design. The sample was the family of tuberculosis patient of first category who was registered to Public Health Center of Blitar city. The sample was 44 respondents selected by simple random sampling. The data collection used the close-ended questionnaire that was developed based on the theory of social support. The result showed that families who had ever received information about nutrition fulfillment was 11.4% (5 families) and had not ever received information was 88.6% (39 families); and the family support to the fulfillment of nutrition of tuberculosis patients of first category was in the category of supportive (59.1%) and non-supportive family was 40.9% (18 families). The correlation value of the Kendall Tau-b was 0.298 (p = 0.014). The family support for the fulfillment of nutrition of tuberculosis patients of first category who support was caused by the information obtained, while who did not support was caused by lack of information about the importance of nutrition fulfillment of tuberculosis patient. A weak correlation was caused by families who had received information about nutrition fulfillment for tuberculosis patients was very little, consequently the support given by the patient as a reward as a family member who was sick was also little. It is recommended that health workers at the Public Health Center give of health education regularly to the family in every drug taking.